LOKAKARYA PENYUSUNAN MODUL PROJEK PENGUATAN PROFIL PELAJAR PANCASILA BAGI GURU KOMITE PEMBELAJARAN SDIT ANNAJIAH LUBUKLINGGAU - Yaspin Yolanda; Andriana Sofiarini; Candres Abadi (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2023)
This activity was held on August 12-13, 2023 involving school facilitators batch 1. The aim of this lokakarya was to strengthen understanding of the implementation of the Pancasila student profile strengthening project (P5) and design ideas for modifying project modules that are in accordance with the context of the situation and needs of the school. Activities using the "Merdeka" flow in the form of elaboration of material, collaboration and reflection and concrete actions of participants. The participants' knowledge achievement was measured by pretest and posttest. The results of the analysis show that the learning achievements of the participants while participating in this lokakarya show that (1) the participants are able to adjust the dimensional elements and the achievement dimensions of each phase, indicating that 90% of the participants understand the concept, 10% do not understand the concept. (2) Participants are able to organize activities in the P5 module using a collaborative project idea design simulation method. The results showed that 90% of the participants understood the concept, 10% did not understand the concept. (3) Participants are able to make a P5 assessment rubric. The results showed that 90% of the participants understood the concept, 10% did not understand the concept. The conclusion is that the average participant's knowledge of the project module to strengthen the profile of Pancasila students is an average percentage. The results show that 90% of the participants understand the concept, 10% do not understand the concept.